Chlorophyll-a Concentration in The Sepinang Lake, Pangkalan Serik Village, Siak Hulu Sub-District, Kampar District, Riau Province. - M Sinaga, Saut; Siagian, Madju; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMany activities arround Sepinang Lake contributes the input of organic and anorganic matter that influence the water quality, especially nutrient concentration in the water. This research was conducted of March – April 2018 in the Sepinang Lake and aims to understand the concentration of chlorophyll-a in the lake. Chlorophyll-a samples were collected from 3 stastions. In each stations there were two sampling sites, in the surface and 2 secchidepth. Sampling was done three times, once a week. Result shown that the chlorophyll-a content ranged from 4.32 µg/L – 9.24 µg/L. Based on the chlorophyll-a concentration, the Sepinang Lake can be categorized as mesotrophic to eutrophic. Water quality parameters values were temperature  30.6 0C - 31.50C, transparency 49.3 cm – 62.8 cm, depth 211 cm – 223.6 cm, DO 4.22 – 5.58 mg/L, CO2 9.32 – 15.98 mg/L  nitrate 0.065 -  0.231 mg/L, phosphate 0.089 – 0.135 mg/L and pH 5.2 – 5.6.Keywords : mesotrophic, water quality, oxbow lake